Teaching Arabic by Gender Perspective at Pesantren Darunnajah - Akmaliyah Akmaliyah; Teti Ratnasih (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2017)
This study was aimed at describing Arabic language teaching which is based on gender perspective at Pesantren Darunnajah Jakarta. Method applied to describe data was inferential descriptive. This method was used to describe, and organize systematically Arabic language teaching at Darunnajah then it drew conclusion based on the data gathered. The findings showed that Arabic language textbook had no material indicating gender bias. The involvement of male and female student in Arabic language material had no bias gender issues. However there was a little content og gender bias when dealing with activities and role of women either visually or textually. Textbook written by D. Hidayat featured: content on text concerning Muhammad SAW history, Siti Khadijah role and Indonesian women activities in the country.